The Influence of Leadership Training on the Performance of State Civil Apparatus at Raden Mattaher Jambi General Hospital - John Eka Powa (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2021)
Leadership Education and Training is one type of training for civil servants in order to support structural positions. This training should be followed by all Officials / Prospective Officers who occupy and/or will occupy structural positions. The success will have an impact on the performance of employees in their respective agencies. This study will examine how much influence leadership education and training have on the performance of the Raden Mattaher Hospital Jambi employees? The population and sample were carried out on the alumni of Post-Education and Training 2016-2020 who served at Raden Mattaher Hospital Jambi as many as 10 people, were selected by persuasive sampling. Data was obtained by distributing questionnaires, then analyzed using a simple regression method processed using SPSS 20. The results of this study are that education and training have a positive and significant effect on employee performance and the effect is in the medium category as shown by the regression equation Y = 0.867X + 12.678 with a regression coefficient (recount) obtained at 0.744 when compared with rtable of 0.351, then rcount> rtable (0.744> 0.351). This shows that the regression coefficient is significant so that Ha in this study is accepted. To improve the performance of Raden Mattaher Hospital Jambi employees in serving the community, it is necessary to suggest that every employee is required to attend training education conducted by educational institutions such as the Jambi Province Human Resources Development Agency.